Tren Konsumsi Fast Food dan Dampaknya terhadap Obesitas di Kalangan Remaja Perkotaan - Muzakir Muhammad Amin; Sulaiman, Sulaiman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The trend of fast food consumption among urban adolescents continues to rise in line with the modern lifestyle that prioritizes convenience. Fast food, which is high in fat, sugar, and sodium but low in fiber and essential nutrients, contributes to the increasing prevalence of obesity. This study aims to analyze the consumption patterns of fast food among adolescents, the factors influencing their preference for fast food, and its impact on obesity. The research employs a qualitative approach with a descriptive method, utilizing literature studies and semi-structured interviews with adolescents and healthcare professionals. The findings indicate that excessive fast food consumption, coupled with a lack of physical activity and poor dietary habits, significantly increases the risk of obesity among adolescents. Obesity not only affects physical health, increasing the risk of diabetes and hypertension, but also impacts mental health and overall quality of life. Therefore, the role of families, schools, and the government is crucial in controlling fast food consumption through nutritional education, the promotion of a healthy lifestyle, and regulations concerning fast food marketing. With appropriate strategies, the unhealthy trend of fast food consumption can be controlled, thereby reducing obesity rates and improving adolescent health quality.